2019
DOI: 10.1016/j.apenergy.2018.12.093
|View full text |Cite
|
Sign up to set email alerts
|

A study of hydrous ethanol combustion in an optical central direct injection spark ignition engine

Abstract: The aim of this experimental work was to improve understanding of the influence of hydrous ethanol on combustion in an engine demonstrating a tendency for biased flame migration towards the hotter exhaust walls as often reported for typical modern pent roof design IC engines. The work aimed to uncover the degree of residual water content that can be reasonably tolerated in terms of combustion characteristics in future ethanol SI engines (with the energy required to reduce water levels then potentially reduced)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The optical results showed that the increase in water content decreased the flame distortion and corrugation. Other combustion visualization study showed that the longer combustion duration resulted from lower apparent flame speed of high water-in-ethanol fuels provided more time for flame front distortion caused by in-cylinder flow characteristics [15]. Iso-octane combustion duration was larger than anhydrous ethanol but faster than any wet ethanol mixture.…”
Section: Introductionmentioning
confidence: 93%
“…The optical results showed that the increase in water content decreased the flame distortion and corrugation. Other combustion visualization study showed that the longer combustion duration resulted from lower apparent flame speed of high water-in-ethanol fuels provided more time for flame front distortion caused by in-cylinder flow characteristics [15]. Iso-octane combustion duration was larger than anhydrous ethanol but faster than any wet ethanol mixture.…”
Section: Introductionmentioning
confidence: 93%
“…However, the high latent heat of ethanol and the presence of water in ethanol that enhances latent heat effects further, reduces air intake charge temperature, and offers higher volumetric efficiency and lower NO X emissions, increases brake thermal efficiency and can decrease unburnt hydrocarbons and CO emissions under certain conditions [13][14][15][16][17]. Some studies have also been performed in optical spark-ignition engines where the decrease in flame speed has been quantified [18,19]. In general 10-15% water content has been considered quite tolerable and with good life-cycle benefits, noting that optimizing engine design to leverage gains in octane number and charge cooling corresponding to water addition on fuel economy could offset the reduction in fuel heating value [20].…”
Section: Use Of Hydrous Ethanol In Enginesmentioning
confidence: 99%
“… 18 This study also did not utilize alternative fuels for the characterization. Other studies performed tests for gaining a deeper understanding of the combustion processes with hydrous ethanol in a single piston test, 19 emissions and combustion efficiency with n-butanol/kerosene in an SI aircraft engine to full load, 20 and studies on general SI engines, with gasoline ethanol and acetylene fuel mixtures only at partial loads for engine combustion and emission analysis 21 among many others. Still, the findings of higher than 10% ethanol–gasoline mixtures over the full range of aircraft engine operation are not completely understood.…”
Section: Introductionmentioning
confidence: 99%